CONSPIRAÇÃO DE ESTADO: O DISCURSO DE GUERRA NA CONSTRUÇÃO DE UM PROJETO ANTICOMUNISTA DE BRASIL (1959-1979) - LIMA, ALCIR DE (2021)
This dissertation deals with the history of military policy in the years of dictatorship and discussions on revolutionary war in Brazil, focusing on military studies developed by the Armed Forces. In military doctrines, the notion of war serves to organize the characteristics and guiding principles of armed institutions, through which it articulates action strategies and the use of its military forces, according to the conditions of each period. In the years after 1945, when the war against Nazi-fascist forces ended, the symbolic effect of the destruction caused by nuclear weapons reopened public discussions about the limits of war as a political instrument. The possibility of a new war between countries that disputed the global political and ideological hegemony put the international community on alert for regional conflicts that could develop into a nuclear war. The international crisis reverberated anti-communism in national crises. The conspiracy theory that enemies infiltrated the country, acting landestinely to carry out the revolution, were ideas that had their origins in French doctrines of volutionary war and were incorporated by armed institutions around the 1960s. When the military interpreted the political crisis as a stage of revolutionary action, according to the indications prescribed by French doctrine, the Armed Forces took power in 1964 and imposed a military dictatorship under the pretext of preventing the communist revolution. The doctrine also underlined the need to strengthen the population's moral and psychological structures, as the fight against communists should also take place through ideological channels, suggesting an anti-communist power project that found a “fertile field” in the Brazilian social imagination. Thus, this dissertation is a contribution both to the history of national politics, as well as to the history of power relations and violence practiced by the State.